Disparities in Access and Sustainability in Inclusive Education Infrastructure in Indonesia - Syarifudin, Fahmi (Proceedings International Conference on Education Innovation and Social Science, 2025)
The present research explores the efforts of Indonesian schools to respond to the realities of inclusive education. Based on a qualitative case study design, data were drawn from interviews, observations, and document analysis in urban, suburban, and rural contexts. The study establishes inclusive education policies, but their operationalization within the schools is a significant issue. Accessibility provisions such as ramps and adjustable classrooms are found to be desirable. In many locations, inadequate teacher preparation often obstructs the effective implementation of assistive technologies. Moreover, most buildings are poorly maintained and experience a rapid quality decline. Teachers tend to acquire inclusive practice through experience and not formal training programs. Although parental involvement is increasing in urban settings, it remains shallow in rural settings. In some areas, schools are forced to get along with the hardships of inclusion on their own, frequently without much assistance from neighboring authorities. Lastly, this study stresses that real inclusion requires effort beyond the simple enactment of policies; it requires ongoing effort in teacher professionalization, well-thought-out infrastructure, more active community participation, and adaptive governance structures. The findings of this study provide valuable lessons on crafting more inclusive and supportive learning environments in Indonesia and elsewher.